PREPARATION OF FUTURE TEACHERS FOR THE INTEGRATION OF MULTIMEDIA TECHNOLOGIES IN THE EDUCATIONAL PROCESS OF MOUNTAIN SCHOOLS OF Carpathians - Kotyk, Tetiana (Mountain School of Ukrainian Carpaty, 2024)
In today’s world, the training of future teachers requires not only pedagogical knowledge but also technical skills for integrating multimedia technologies into the educational process, especially in remote mountain schools. The article presents the results of an analysis of scientific literature on the technical skills necessary for teachers to effectively use multimedia in teaching. It has been identified that successful integration of multimedia tools requires teachers to be proficient in using presentation software (PowerPoint, Google Slides), editing and integrating video and audio files, applying online platforms (Moodle, Google Classroom), and managing videoconferencing (Zoom, Microsoft Teams). The successful preparation of students also depends on the teacher's ability to create interactive tasks using gamification elements and to analyze results through testing platforms. The authors emphasize that for distance learning, a teacher’s ability to facilitate active online interaction with students and parents is crucial, managing video conferences, integrating multimedia into teaching materials, and maintaining a high level of student engagement in the learning process. This requires deep knowledge of multimedia content editing (video, audio), the use of simulations and interactive programs, and adherence to copyright regulations. Thus, the preparation of future teachers should include training in multimedia work, which will significantly improve the quality of education in the mountain schools of the Carpathian region and enhance students' communication skills.